A novel CCCH‐type zinc finger protein SAW1 activates OsGA20ox3 to regulate gibberellin homeostasis and anther development in rice. Issue 10 (10th April 2020) - Wang, Bin; Fang, Ruiqiu; Chen, Faming; Han, Jingluan; Liu, Yao‐Guang; Chen, Letian; Zhu, Qinlong
Abstract: Male sterility is a prerequisite for hybrid seed production. The phytohormone gibberellin (GA) is involved in regulating male reproductive development, but the mechanism underlying GA homeostasis in anther development remains less understood. Here, we report the isolation and characterization of a new positive regulator of GA homeostasis, swollen anther wall 1 ( SAW1 ), for anther development in rice ( Oryza sativa L.). Rice plants carrying the recessive mutant allele saw1 produces abnormal anthers with swollen anther wall and aborted pollen. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRIPSR‐associated protein 9‐mediated knockout of SAW1 in rice generated similar male sterile plants. SAW1 encodes a novel nucleus‐localizing CCCH‐tandem zinc finger protein, and this protein could directly bind to the promoter region of the GA synthesis gene OsGA20ox3 to induce its anther‐specific expression. In the saw1 anther, the significantly decreased OsGA20ox3 expression resulted in lower bioactive GA content, which in turn caused the lower expression of the GA‐inducible anther‐regulator gene OsGAMYB . Thus, our results disclose the mechanism of the SAW1 ‐ GA20ox3‐GAMYB pathway in controlling rice anther development, and provide a new target gene for the rapid generation of male sterile lines by genome editing for hybrid breeding. Abstract : A novel nucleus‐localized CCCH‐tandem zinc‐finger transcription factor SAW1 enhances the expression of anther‐specific OsGA20ox3 for GA homeostasis and anther development in rice. Loss‐of‐function of SAW1 significantly decreases OsGA20ox3 expression leading to low bioactive GA content and low expression of GA‐inducible gene OsGAMYB during anther development.